Gertrude Stein and the politics of participation : democracy, rights and modernist authorship, 1909-1933 - Parkinson, Isabelle (Edinburgh University Press, 2023)
"This book explores the politics of the right to write in Gertrude Stein's practice and its reception. It examines how conceptions of authorship intersected discourses of democracy and rights in the period 1909-1933. The persistent debates across a broad range of publication contexts over Gertrude Stein's right to participate in modernist authorship provide an instructive example of the way literary culture reflected contemporary political discussion. This study explores how representations of Stein that figured her either as barely human or as the ultimate democratic subject reproduced debates about who should participate in public life, refracted an emerging discourse of human rights, and echoed fears about the consequences of mass democracy as political franchise was extended"-- Provided by publisher.
Keywords: Stein, Gertrude, -- 1874-1946 -- Criticism and interpretation.; Stein, Gertrude, -- 1874-1946 -- Political and social views.; Stein, Gertrude, -- 1874-1946; Literary studies: fiction, novelists & prose writers.; Literature: history & criticism.; Literature & literary studies.; LITERARY CRITICISM / American / General.; Political and social views; Literature.; Electronic books.; Literary criticism; Criticism, interpretation, etc.; Literary criticism.; Critiques littéraires.